Timing of return from altitude training for optimal sea level performance - Chapman, R. F.; Laymon Stickford, I. S.; Lundby, C.; Levine, B. D. (Journal of Applied Physiology, 2014)
While a number of published studies exist to guide endurance athletes with the best practices regarding implementation of altitude training, a key unanswered question concerns the proper timing of return to sea level prior to major competitions. Evidence reviewed here suggests that, altogether, the deacclimatization responses of hematological, ventilatory, and biomechanical factors with return to sea level likely interact to determine the best timing for competitive performance.